Determinant Stock Liquidity with Asymmetric Information as Intervening Variables in Property and Real Estate Companies Listed on the Indonesia Stock Exchange - Rina Dameria Napitupulu; Tri Widyastuti; Zulkifli (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of financial strategy, capital expenditure, and earnings growth on stock liquidity through the role of information asymmetry as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange. Stock liquidity is identified as a crucial element in equity market stability, where information asymmetry often challenges the main factors influencing stock trading activity. The methodology used involves secondary data analysis of major property board companies during the period 2018-2023. Data were analyzed using a structural equation modeling (SEM PLS) approach to identify direct and indirect relationships between the studied variables. The results show that financial strategy and capital expenditure have a positive effect on stock liquidity, both directly and through information asymmetry. Earning growth contributes significantly to reducing information asymmetry, which ultimately increases stock liquidity. These findings support the importance of information transparency and strategic management as a means to increase investor confidence and market stability. This study provides an in-depth overview of stock liquidity dynamics in the context of the property and real estate market listed on the Indonesia Stock Exchange, highlighting the critical role of strategic information management. It also recommends the implementation of policy transparency and effective communication strategies to mitigate the negative impact of information asymmetry.